Gomphocythere besni n. sp. (Crustacea, Ostracoda) from a man-made pool (Adıyaman, Turkey) - Külköylüoğlu, Okan; Yavuzatmaca, Mehmet; Cabral, Maria Cristina; Colin, Jean-Paul (Zootaxa, 2015)
We describe a new species (Gomphocythere besni n. sp.) from the Tavaş man-made pool in Besni town (Adıyaman, Turkey). The species has several differences from its congeners in furcal structures (forked organ, seta of caudal ramus), numbers of setae on maxillula and maxillular palp, particular ornamentation with up to eight fossae in each mesh of the reticulation and in the presence of two types of lateral pore-canals (single pore opening with a sensillum and sieve plates) on the carapace. The finding of the new species extends the known geographical distribution of the living forms of the genus further to the North. The new species was found from relatively cool (16.6 ºC) and medium oxygenated waters (7.36 mg/L) in a mixture of sand and gravel substrate. Details about its ecology and taxonomic status are also compared and discussed with other species of the same genus.